Business Model Canvas: Perencanaan Strategi Pengembangan Agrowisata Belimbing Karangsari Kota Blitar di Masa Pandemi Covid-19 - Muhammad Diaudin; Nasikh (Media Wisata, 2022)
Business Model Canvas: Strategy Planning For The Development Of Karangsari Star Agro-Tourism In Blitar City During The Covid-19 Pandemic. This study aims to determine a strategic plan for the development of Karangsari Starfruit Agrotourism during the COVID-19 pandemic. The method in this research is descriptive qualitative with a Business Model Canvas approach and SWOT analysis. The results of this study are an overview of the current Business Model Canvas from Karangsari Belimbing Agrotourism and a development strategy plan that is prepared based on a SWOT analysis on each Business Model Canvas block. The resulting strategic plan is to expand the target audience, add photo spot facilities and rest areas, add new social media for marketing, utilize social media to establish good relations with visitors, manage social media content consistently, increase collaboration, utilize empty areas and improve quality. HR, reducing variable costs according to priority needs, and increasing income from existing sources.